Effect of Paired-Pulse Electrical Stimulation on the Activity of Cortical Circuits - Saito, Kei; Onishi, Hideaki; Miyaguchi, Shota; Kotan, Shinichi; Fujimoto, Shuhei (Frontiers in Human Neuroscience, 2015)
Objective: We investigated the transient effect of short-duration paired-pulse electrical stimulation (ppES) on corticospinal excitability and the after-effect of long-duration ppES on excitability, short-latency afferent inhibition (SAI), and afferent facilitation (AF). Methods: A total of 28 healthy subjects participated in two different experiments. In experiment 1, motor-evoked potentials (MEPs) were measured in the abductor pollicis brevis (APB) and abductor digiti minimi (ADM) muscles before and immediately after short-duration ppES (5 s) at various inter-pulse intervals (2, 3, 4, 5, 6, 7, 10, 15, 20, and 30 ms). In experiment 2, MEPs, SAI, and AF were measured before, immediately, and 20 min and 40 min after long-duration ppES (20 min, inter-pulse interval of 5 ms and 15 ms) and peripheral electrical stimulation (20 min, 10 Hz and 20 Hz). Results: Short-duration ppES with inter-pulse intervals of 5 and 20 ms significantly increased MEP measured in APB but not in ADM. Long-duration ppES with an inter-pulse interval of 5 ms significantly decreased SAI but not MEPs in APB. In contrast, long-duration ppES did not affect ADM. Conclusion: The afferent inputs induced by ppES-5 ms were effective for transiently increasing MEP and sustaining SAI reduction.